Situating Local Knowledge Within Development Agenda: Some Reflections - Dare, Kolawole, Oluwatoyin (Consilience, 2009)
The paper endeavors to personify development and shows the multi-dimensionality of the concept. It argues against the power relations influencing knowledge production while attempting to shed light on what knowledge is all about. It provides a range of definitions of local knowledge (LK), presents its stages of production and expressly buttresses the importance of LK in the agenda-setting for development initiatives. The paper also argues that the framing and labeling of LK and its custodians by outsider-professionals in connivance with their insider-expert colleagues have been one of the challenges to placing a premium on local knowledge within the development agenda. While emphasizing the need for stakeholders’ partnership to enable working towards congruence in the midst of chaos and order, the paper calls for a more eclectic approach and reflexivity amongst development experts when drawing the agenda for development programs. It also advocates for the codification and teaching of local knowledge in Universities and Colleges.